Calculation of ISON Cometary Tail Temperature - Khalaf, Salman (Iraqi Journal of Science, 2023)
The ion tail temperature of the comet ISON was calculated by using magneto-hydrodynamic MHD laws. From these equations the focus is concentrating on determine the ion tail temperature from the relations of dynamic and static pressures results.MHD equations are numerically solved using Matlab simulation code using cubic volume element method, based on three dimensionl Cartesian coordinates that devided into equal 15x15x15 equally spaced mesh. The simulation was performed using 3-D Lax explicit method considering normalised physical propreties relative to those of the solar wind at 1 AU. The results explained that it is possible to deduce two types of temperature, the first being the isotropic temperature which is shown to vary slowly with distance from the cometary nucleus. The second type which is the dynamic temperature is shown to change continouosly and largely with distance from the cometary nucleus.